2001
DOI: 10.1007/s003300000760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contrast dilution on contrast-enhanced MR angiography of the aorta and renal arteries

Abstract: The aim of this study was to investigate the effect of gadolinium chelate dilution on vascular enhancement in contrast-enhanced two-dimensional (2D) MR subtraction angiography of aorta and renal arteries. Twenty patients were prospectively included. 2D subtraction MR angiography consisted of successive multisection breathhold GRE acquisitions of 16 s (2D FLASH, TR/TE 72/4, flip angle 60 degrees) obtained in the coronal plane before and after intravenous bolus administration of 0.1 mmol/kg BW gadolinium chelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Apparently, the dose increase from 0.1 to 0.2 mmol/kg bodyweight does not provide better image quality or higher contrast enhancement in the carotids. Our findings are in agreement with those of similar studies [10,12,14,15], most of which were realized with volunteers. No significant difference between a single dose, a double dose and a triple dose was found in CE-MRA of the aorta with respect to quantitative signal enhancement and qualitative interpretation [10].…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…Apparently, the dose increase from 0.1 to 0.2 mmol/kg bodyweight does not provide better image quality or higher contrast enhancement in the carotids. Our findings are in agreement with those of similar studies [10,12,14,15], most of which were realized with volunteers. No significant difference between a single dose, a double dose and a triple dose was found in CE-MRA of the aorta with respect to quantitative signal enhancement and qualitative interpretation [10].…”
Section: Discussionsupporting
confidence: 96%
“…Despite the success of CE-MRA, only a few studies have addressed the question of optimal gadolinium dose [4,[7][8][9][10][11][12][13][14] comparing various dose groups for the renal [4] or major abdominal arteries [8,10,[12][13][14]. Most authors have tried to address the question by measuring peak enhancement for volunteers [10,[12][13][14][15], but only a few studies have compared the quantitative contrast enhancement within patients [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…12,32 Approximately 70 to 90 seconds after administration of a full dosage of Gd-DOTA, we observed a significant decrease of SI within inner medulla and renal pelvis, which was also noted on time-intensity curves. 6,[33][34][35][36][37] In those studies, an assumption was made that the relationship between SI and the tissue concentration of the contrast agent was unaffected by changes of T2 and T2*, allowing conversion of arbitrary SI curves into quantitative units using the inverse relationship between T1 and concentration of contrast agent. 9 This phenomenon is presumably related to the contributed T2 and T2* effects found at levels of contrast-agent concentration above a given threshold, as previously reported 6 and supported by the results of our phantom study (25 mmol Gd/ L Ϫ1 for Gd-DOTA and 3.5 mmol Gd/L Ϫ1 for P792).…”
Section: Functional Analysis and Role Of Gd-dota Concentrationmentioning
confidence: 99%
“…However, Goyen et al (11) reported that the image quality of CE‐3D‐MRA using 1.0 mol/L gadolinium chelate showed no statistically significant improvement compared to using 0.5 mol/L gadolinium chelate, and suggested that the concentration of gadolinium chelate might have little effect upon image quality. Dilution is thus one alternative for reducing the total dose of gadolinium chelate, but to our knowledge there have been few reports evaluating the effect of gadolinium chelate dilution on vascular enhancement in CE‐3D‐MRA (12).…”
mentioning
confidence: 99%